The pitch angle control of variable speed wind turbine using PID controller - Josyula s l tejaswi, Y. Bhanu Chandra M.E (International Journal of Scientific Research and Management (IJSRM), 2015)
This paper presents the Pitch angle control of Permanent Magnet Synchronous Generator (PMSG) based on Wind Energy Conversion System (WECS) using PID control technique. The models of WECS consist of a wind turbine, pitch angle control, pitch actuator, drive train, PMSG and power converter. Wind turbine model with controller for generator protection in high wind speed is also presented in this paper. The PMSG and converter model are established. The presented model, simulation results are tested in MATLAB/SIMULINK